Gambaran Perilaku Tutor dan Efektifitas Kelompok Tutorial di Fakultas Kedokteran Universitas HKBP Nommensen Medan Tahun Ajaran 2022/2023 - Purba, Ogi; Zaluchu, Ristarin; Simorangkir, Saharnauli (Nommensen Journal of Medicine, 2025)
Background: One of the components of the SPICES approach is Problem-Based Learning (PBL). The Faculty of Medicine at HKBP Nommensen University in Medan has implemented this PBL system in a tutorial activity. Several benefits of the above tutorial activity can be achieved if the tutorial runs effectively. An effective tutorial activity is one where its objectives can be achieved as expected. According to several studies, the tutor and students can influence the effectiveness of the tutorial activity.1,2,3,4 Even Indonesian culture can affect the effectiveness of the tutorial.5 Therefore, the researcher wants to conduct a study on the description of tutor behavior and the effectiveness of tutorial groups at the Faculty of Medicine, HKBP Nommensen University in Medan, Academic Year 2022/2023. Objective: Describe the behavior of tutors and the effectiveness of tutorial groups at the Faculty of Medicine, HKBP Nommensen University in Medan, Academic Year 2022/2023. Methods: This research is a descriptive study and a sample size of 179 students. Data were analyzed using the Chi-square test. Results: There is a relationship between premenstrual syndrome and insomnia among female students at SMA Negeri 2 Medan. The level of tutor behavior in terms of social congruence, cognitive congruence, subject-matter expertise, and the level of tutorial group effectiveness based on students' perceptions at the Faculty of Medicine, HKBP Nommensen University in Medan, Academic Year 2022/2023, is high. Conclusion: There is relationship between premenstrual syndrome with insomnia symptom towards female students of SMA Negeri 2 Medan.